Investigation of the GnRH antagonist degarelix isomerization in biological matrices - Lucia Ferrazzano; Alessandra Tolomelli; Ivan Guryanov; Marco Macis; Ulrich Abel; Antonio Ricci; Walter Cabri (Wiley, 2023)
Abstract One of the main objectives of peptide drug design is the improvement of peptide pharmacokinetics with maintaining biological activity, which can be achieved by the complex modifications of the primary structure of the peptides. However, these changes often lead to the formation of peculiar impurities in the peptide drugs and their metabolites, which require the development of advanced analytical methods to properly assess their content. Here, we investigated the degradation of the potent long‐acting GnRH antagonist degarelix in various biologic media by the tailor‐made HPLC method, which allows precise determination of 5‐Aph(Hyd)‐degarelix isomer, an impurity found in the degarelix active pharmaceutical ingredient (API) during its manufacturing. Unexpectedly, we discovered a rapid and irreversible conversion of degarelix API into the corresponding hydantoin isomer in serum, suggesting that this impurity can be also a potential drug metabolite in vivo. This finding underlines the importance of the development of more accurate and performing analytical techniques to correctly characterize the chemical composition of the manufactured drugs and their behavior under physiological conditions.